Characterizing and comparing the spawning habitats of sardine (Sardinops sagax) and anchovy (Engraulis encrasicolus) in the northern Benguela region - Tjizoo, Mbeurora Beau (Department of Biological Sciences, 2014)
Includes bibliographical references (p. 101-115).